Methodology Towards Computer-aided Testing of Complex Mechatronic Systems: A Case Study about Assembling a Train System - Meinel, David; Paryanto, Paryanto; Franke, Jörg (Procedia CIRP, 2016)
Domain-specific computer-aided analysis of technical systems has become well-established. Nominal and worst case scenario behavior of systems can be modelled sufficiently, however, still lacking the ability of simulating the behavior of technical systems as a whole, combining single-domain subsystems. Therefore, unpredictable failure can occur, which displays the demand for computer-aided system analysis. To counteract the foresaid, a concept has been proposed, which enables sufficient designing and implementing a highly flexible model landscape. It serves the process from comprehending a technical system's specifications and functions towards an executable model structure, using the Modelica-based modelling software SimulationX. Since its future application remains to be tested in the aftermath, the concept will exemplarily be applied on a flexible train simulator.
CRIS-Team Scopus Importer:2023-03-07
Keywords: Computer-aided testing; Flexible simulator; Mehatronic system modelling; SimulationX; Train modelica; Train simulator; Train systems